Insights Into Peptide Inhibition of Alpha-Synuclein Aggregation - Torpey, James H.; Meade, Richard M.; Mistry, Ravina; Mason, Jody M.; Madine, Jillian (Frontiers in Neuroscience, 2020)
α-Synuclein (aSyn) aggregation is an attractive target for therapeutic development for a range of neurodegenerative conditions, collectively termed synucleinopathies. Here, we probe the mechanism of action of a peptide 4554W, (KDGIVNGVKA), previously identified through intracellular library screening, to prevent aSyn aggregation and associated toxicity. We utilise NMR to probe association and identify that 4554W associates with a ‘partially aggregated’ form of aSyn, with enhanced association occurring over time. We also report the ability of 4554W to undergo modification through deamidation of the central asparagine residue, occurring on the same timescale as aSyn aggregation in vitro, with peptide modification enhancing its association with aSyn. Additionally, we report that 4554W can act to reduce fibril formation of five Parkinson’s disease associated aSyn mutants. Inhibitory peptide binding to partially aggregated forms of aSyn, as identified here, is particularly attractive from a therapeutic perspective, as it would eliminate the need to administer the therapy at pre-aggregation stages, which are difficult to diagnose. Taken together the data suggest that 4554W could be a suitable candidate for future therapeutic development against wild-type, and most mutant aSyn aggregation.